Redescription of the genus Manta with resurrection of Manta alfredi (Krefft, 1868) (Chondrichthyes; Myliobatoidei; Mobulidae) - Marshall, Andrea D.; Compagno, Leonard J. V.; Bennett, Michael B. (Zootaxa, 2009)
The taxonomic history of the genus Manta has been questionable and convoluted, with Manta having one of the most extensive generic and species synonymies of any living genus of cartilaginous fish. Having previously been considered a monotypic genus with a single recognized species, Manta birostris (Walbaum 1792), new evidence, in the form of morphological and meristic data, confirm that two visually distinct species occur, both with wide ranging distributions through many of the world’s oceans. Manta birostris stands as the most widely distributed member of the genus, while Manta alfredi (Krefft 1868), resurrected herein, represents a smaller, more tropical species. Separation of the two species is based on morphometric measurements and external characters including colouration, dentition, denticle and spine morphology, as well as size at maturity and maximum disc width. The two species of Manta are sympatric in some locations and allopatric in other regions. A visual key was constructed which highlights the conspicuous, diagnostic features of the two species using data collected throughout their respective geographical ranges. A third, putative species, referred to here as Manta sp. cf. birostris, in the Atlantic may be distinct from M. birostris, but further examination of specimens is necessary to clarify the taxonomic status of this variant manta ray. The results of this study will aid in the differentiation of members of this genus both in the field and in preserved specimens. The splitting of this long-standing monospecific genus will help to highlight the specific threats facing the different species of Manta (e.g. targeted fishing, bycatch fisheries, boat strikes and habitat degradation) and will ultimately assist in the correct assessment of their respective worldwide conservation status.